The Impact of Price on the Profits of Fishermen Exploiting Tritrophic Prey-Predator Fish Populations - Meriem Bentounsi; Imane Agmour; Naceur Achtaich; Youssef El Foutayeni (International Journal of Differential Equations)
We define and study a tritrophic bioeconomic model of Lotka-Volterra with a prey, middle predator, and top predator populations. These fish populations are exploited by two fishermen. We study the existence and the stability of the equilibrium points by using eigenvalues analysis and Routh-Hurwitz criterion. We determine the equilibrium point that maximizes the profit of each fisherman by solving the Nash equilibrium problem. Finally, following some numerical simulations, we observe that if the price varies, then the profit behavior of each fisherman will be changed; also, we conclude that the price change mechanism improves the fishing effort of the fishermen.